2008
DOI: 10.1166/jnn.2008.145
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Sulphide (CdS) Nanotechnology: Synthesis and Applications

Abstract: Over the past few years there has been sustained interest in the synthesis, characterization and application of cadmium sulphide (CdS) nanostructures such as nanoparticles, nanowires, nanobelts, nanospheres. The history of CdS, more recent advances in the chemistry and synthesis of CdS nanostructures, and their application as nanoscale devices in diverse technology areas from electronics to targeted drug delivery is described. Although the focus is on CdS, the review provides an excellent overview of the mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 0 publications
2
61
0
Order By: Relevance
“…This type of behavior is commonly observed in nanosized particles [14]. The comparison of XRD peak profile and the 2θ position of diffraction peaks (Table 1) with standard ASTM data confirms the wurtzite (α-CdS) crystal structure with the preferential orientation along (0 0 2) plane [10]. An additional peak at 2θ = 31.33°has also been detected which corresponds to hcp CdO [27].…”
Section: Structural Characterization By X-ray Diffractionsupporting
confidence: 62%
See 3 more Smart Citations
“…This type of behavior is commonly observed in nanosized particles [14]. The comparison of XRD peak profile and the 2θ position of diffraction peaks (Table 1) with standard ASTM data confirms the wurtzite (α-CdS) crystal structure with the preferential orientation along (0 0 2) plane [10]. An additional peak at 2θ = 31.33°has also been detected which corresponds to hcp CdO [27].…”
Section: Structural Characterization By X-ray Diffractionsupporting
confidence: 62%
“…This may point out that the synthesized CdS nanoparticles are rich in Cd content. The intensity of diffraction peaks (Table 1) has been observed to be low as compared to bulk CdS [10]. It is also observed that the positions of diffraction peaks for CdS nanoparticles shift to higher diffraction angles in comparison to bulk CdS.…”
Section: Structural Characterization By X-ray Diffractionmentioning
confidence: 90%
See 2 more Smart Citations
“…Because the novel properties of nanomaterials depend on their size, structure and shape, an understanding of their mechanism as well as a new direction for synthetic methods are significant issues in nanoscience and nanotechnology (White et al 2009). As a result of the high surface-to-volume ratio of the nanoparticles, the surface properties have significant effects on their structure, and in turn, have an influence on the nanoscale devices in electronics to target in drug delivery (Hullavarad et al 2008). In recent years, semiconductor nanoparticles exhibit specific properties due to the quantum confinement effects.…”
Section: Introductionmentioning
confidence: 99%